1986
DOI: 10.1104/pp.82.2.625
|View full text |Cite
|
Sign up to set email alerts
|

Protoplasmic Swelling as a Symptom of Freezing Injury in Onion Bulb Cells

Abstract: Freezing injury, in onion bulb tissue, is known to cause enhanced K' efflux accompanied by a small but significant loss of Ca2" following incipient freezing injury and swelling of protoplasm during the postthaw secondary injury. The protoplasmic swelling of the cell is thought to be caused by the passive influx of extracellular K' into the cell followed by water uptake. Using outer epidermal layer of unfrozen onion bulb scales (Allium cepa L. cv Big Red), we were able to stimulate the irreversible freezing inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…The uniqueness of calcium as a second messenger in mediating many metabolic responses and in membrane stability in plant cells is well established (6,9,10,23). Furthermore, our earlier studies have suggested a role of calcium in freezing injury (1,2). Therefore, in the present study, we examined the role of calcium rather than other divalent cations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The uniqueness of calcium as a second messenger in mediating many metabolic responses and in membrane stability in plant cells is well established (6,9,10,23). Furthermore, our earlier studies have suggested a role of calcium in freezing injury (1,2). Therefore, in the present study, we examined the role of calcium rather than other divalent cations.…”
Section: Discussionmentioning
confidence: 99%
“…Medium-sized onion bulbs were frozen by cooling at the rate of 1.5°C/h, to either -8.5°C ± 0.5°C or -11.5°C ± 0.5°C, and then were thawed slowly over ice (2,15). To prevent supercooling, bulbs were nucleated at -1°C.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations